Organization aspects of distance learning in postgraduate training the specialists of pharmacy National University of Pharmacy - Tolochko, V. M.; Zarichkova, M. V.; Mishchenko, I. V.; Medvedyeva, Y. P.; Толочко, В. М.; Зарічкова, М. В.; Міщенко, І. В.; Медведєва, Ю. П.; Заричковая, М. В.; Мищенко, И. В.; Медведева, Ю. П. (ЗДМУ, 2014)
The article is dedicated to study organization aspects of distance learning (DL) implementation into postgraduate training the specialists of practical pharmacy, based on the experience of Management and Economics of Pharmacy Department of Institute of Pharmacy Specialists’ Professional Development, National University of Pharmacy. The 5 main steps of implementation have been described; its content and meaning have been studied. It was accented, that it is necessary to elaborate the uniﬁ ed approach for evaluation of educational and methodical work, its registration with the right to issue the state certiﬁ cate. The readiness for practical implementation of DL after the completion of last preparatory period at the state level has been marked. Вивчили організаційні аспекти впровадження дистанційного навчання у післядипломну освіту спеціалістів практичної фармації на прикладі досвіду кафедри управління та економіки фармації Інституту підвищення кваліфікації спеціалістів фармації Національного фармацевтичного університету (м. Харків). Визначили п’ять основних етапів упровадження, дослідили зміст і значення кожного з них. Звернули увагу на необхідність розробки єдиних підходів до обліку навчальної та навчально-методичної роботи, її оформлення із правом видачі документа державного зразка. Визначили готовність до практичного впровадження дистанційного навчання після завершення останнього підготовчого етапу на державному рівні. Изучены организационных аспектов внедрения дистанционного обучения в последипломное обучение специалистов практической фармации на примере опыта кафедры управления и экономики фармации Института повышения квалификации специалистов фармации Национального фармацевтического университета (г. Харьков). Определены пять основных этапов внедрения, исследовано содержание и значение каждого из них. Акцентируется внимание на необходимости выработки единых подходов к учету учебной и учебно-методической работы, ее оформления с правом выдачи документа государственного образца. Отмечена готовность к практическому внедрению дистанционного образования при завершении последнего подготовительного этапа на государственном уровне.
Організаційні аспекти дистанційного навчання в післядипломній освіті спеціалістів фармації
Организационные аспекты дистанционного обучения в последипломном образовании специалистов фармации
Keywords: distance learning (DL); postgraduate training the specialists of pharmacy; thematic improvement; дистанційне навчання; післядипломна освіта спеціалістів фармації; тематичне удосконалення; дистанционное обучение; последипломное образование специалистов фармации; тематическое усовершенствование